Interrelations of rainfall and morphometric characteristics in generating geological disasters of Kuranji watershed Padang city. Issue 1 (April 2021) - Putra, T H A; Istijono, B; Aprisal; Rusman, B; riani; Hakam, A; Adrinal; Ophiyandri, T
Abstract: The Kuranji watershed is one of the watersheds in the city of Padang, which is currently experiencing development due to rapid population growth. This has resulted in land conversion from areas that have vegetation to built areas such as settlements. This affects the balance of the Kuranji watershed ecosystem and can lead to geological disasters. Therefore an initial analysis is needed in the development of the Kuranji watershed in the future. This study aims to analyse the interrelation of rainfall and morphometric characteristics that have an impact on geological disasters. The data used are data of maximum rainfall and maximum river discharge in the Kuranji watershed from 2009 - 2018. DEM data (30x30) used to calculate morphometric aspects, consisting of linear aspects, area aspects and relief aspects. The calculation of these aspects is done by a Geographic Information System (GIS) approach using ArcGIS 10.6 software. The result shows that the Kuranji watershed has an area of 22469, 55 ha with dendritic drainage patterns. The linear aspect reveals that it has 1894 rivers with a total length of 774, 6 km. This aspect explains that with the many tributaries, the Kuranji watershed has the potential to cause flooding. Aspects of the area explain that the Kuranji watershed has an elongated shape, steep slope and causes a rapid and large run-off discharge. Drainage density is at medium level with a value of 3, 45 (km/km2) which is close to the high category. The higher the drainage density the smaller the chance of water for infiltration and the greater the river discharge. The relief aspect explains that the Kuranji watershed has a height between 0-1860 meters above sea level. Relief ratio and gradient ratio have a value of 0, 08. Gradient ratios with high values result in fast and swift flow of surface and river water flow. This has the potential for landslides, channel erosion and river wall erosion. High rainfall, extreme morphometric characteristics, causes the Kuranji watershed to have a great potential for geological disasters.